Revitalization of the Symbolic Meaning and Aesthetic Culture of Lesung Panjang in the Kinali - Rajif Ayunda; Rosminda Rosminda; Asril Asril; Dede Pramayoza; Shofi Nurhayati (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
This research departs from the problem of the fading tradition of the Lesung Panjang tradition in Mandi Angin, Kinali District, Pasaman Barat, Sumatera barat, Indonesia as a result of changes in technology and people's lifestyles. The long mortar, which used to function as a tool for processing communal rice as well as a medium for forming the value of togetherness, symbolism, and sound aesthetics, now only appears in a limited way in traditional activities. The urgency of this research lies in the urgent need to revitalize the long dlet not only as a cultural object, but as an intangible cultural heritage that contains visual, social, and symbolic value. The research gap was found in the lack of studies that placed Lesung Panjang in the perspective of fine arts and multisensory aesthetics, especially related to visual forms, sound rhythms, and accompanying social structures. This research aims to re-examine the symbolic meaning, aesthetic value, and social function of long dimples through an art approach as a cultural revitalization strategy. The research method uses a descriptive qualitative approach with an ethnographic design of art. The data source consists of primary data in the form of observations and in-depth interviews with community leaders, as well as secondary data in the form of documentation and literature studies. Data collection techniques include observation, interviews, and documentation, with data analysis through reduction, presentation, and conclusion drawn, as well as testing the validity of data using source triangulation. The results of the study showed that the Lesung Panjang has a strong visual and sound aesthetic value, representing the collective work structure and symbolic value of society. This research contributes to enriching the study of cultural revitalization based on fine art and recommends further research on the development of educational media and art works based on local traditions.